Implementation of effective communication in interprofessional collaboration to improve inpatient services - B, Syarif; Dg. Palallo, Umar; Herman, Sriyana (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Interprofessional Collaboration (IPC) is an interprofessional collaboration between people with different professional backgrounds who work together to solve health problems and provide health services. This research aims to analyze the implementation of effective communication in interprofessional collaboration to improve inpatient services. Research Methodology: The research is qualitative with a phenomenological design. Six people were the research informants: hospital leadership, PMKP, medical committee, medical service element, nursing element, and medical support element. Data will be collected using observation, FGD, in-depth interviews, and document study. Data processing and analysis use the Miles and Huberman method. Result: The study's results indicate that the implementation of IPC still needs improvement. Lack of practical communication skills is the leading cause of IPC being less than good. Management efforts to improve helpful communication skills include providing training related to effective communication, forming an evaluation team, and giving rewards and punishments. Conclusion: Management is making efforts to improve effective communication skills by providing training related to effective communication, forming an evaluation team, and giving rewards and punishments. Health workers are making efforts to comply with all rules that have been given by management to support an effective communication program for patients and between health workers